The Effectiveness of Pregnancy Exercise on Anxiety of Primigravida Mothers at The Galang Mother's Love Clinic - Wulan, Sri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Congestion experienced by pregnant women can cause various negative impacts on their mental and physical health. High anxiety often contributes to mental disorders, such as depression, which can disrupt a mother's mood and emotional well-being. In addition, the stress response that arises from anxiety can result in physical problems, such as headaches, sleep disorders, and digestive problems, which ultimately impact the immune system. This study aims to assess the effectiveness of pregnancy exercise in reducing anxiety in primigravida mothers at the Kasih Ibu Galang Clinic. The method used was a quantitative study with a pretest-posttest design, involving 15 respondents who took part in a pregnancy exercise program for six weeks. Anxiety levels were measured before and after the intervention using an anxiety scale. The research results showed that the average anxiety level of respondents before participating in pregnancy exercise was 1.67, while after the intervention it decreased to 1.20. Statistical analysis produced a p-value of 0.029, which indicated a significant reduction in anxiety levels. These findings indicate that pregnancy exercise is effective in reducing anxiety in primigravida mothers, so it is recommended as an intervention to support mental health during pregnancy.